A new species and a new record of the spider genus Nesticus (Araneae, Nesticidae) from southern Brazil - Estol, Narelle; Rodrigues, Everton Nei Lopes (Zootaxa, 2017)
The spider family Nesticidae includes 233 species in 13 genera and is distributed almost worldwide (World Spider Catalog, 2016). However, the family is still poorly known in the Neotropical Region. The genus Nesticus Thorell, 1869 comprises 132 species and seven subspecies and was described based on N. cellulanus (Clerck, 1757), from Europe (World Spider Catalog, 2016). Meridional South American species of Nesticus were revised by Ott & Lise (2002). More recently, Faleiro & Santos (2011) described a new species from the state of Minas Gerais, Brazil and Torres et al. (2016) a new species from the province of Salta, Argentina. Nowadays, Nesticus is represented by six species in Brazil: Nesticus brasiliensis Brignoli, 1979; Nesticus brignolii Ott & Lise, 2002; Nesticus calilegua Ott & Lise, 2002; Nesticus ivone Faleiro & Santos, 2011; Nesticus potreiro Ott & Lise, 2002 and Nesticus taim Ott & Lise, 2002 (World Spider Catalog 2016).